Ultrasound-guided genicular nerve blocks for acute knee pain in the emergency department: A case series - Carlos Gonzalez-Cobos; Gabriel Rose (JEM Reports)
Background: Acute knee pain is a common presentation in the emergency department (ED), often necessitating effective and rapid pain relief to improve patient mobility and quality of life. Traditional analgesics may be insufficient, and regional anesthesia, such as genicular nerve blocks (GNB), offers a promising opioid-sparing alternative. Objective: We present a case series of two patients who were successfully treated using ultrasound-guided GNB in the ED for acute knee pain. Discussion: Ultrasound-guided GNB offers rapid pain relief, preserves motor function, and reduces the need for opioid analgesics. Further studies are warranted to confirm these findings and explore the broader applicability of this technique in emergency medicine. Conclusion: Ultrasound-guided GNB is an effective and safe method for managing acute knee pain in the ED.